(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
In India, Floating structures are deficient as maximum construction is done on land. But due to high rate of increasing population we need an alternative for our future generations. It has been successfully confirmed that we can built floating structures that can float on water. Many structures have been constructed so far by different countries. Floating structures like docks, floating islands, floating supermarkets, floating terminals, airports etc. have been constructed and are functioning successfully. In India we are lacking the concept of floating structures which can help us to reserve land and use water bodies for the construction. Firstly, we need to adopt floating structures as an alternative for the structures like airports, terminals, as they require more land and then later, we can shift to other types of floating structures. The main objective of our study is to develop such a concrete that can float in water (i.e., low density concrete) and that is possible only when the density of our concrete is less than that of water that is less than 1000kg/m3Along with the lesser density it should fulfill the strength requirements both compressive as well as flexural strength. One of the most important objective of our study is that we are using light weight aggregates like glass beads and pumice stone as an alternative to the coarse aggregate along with sand. We are also using Aluminium powder in order to increase porosity of our concrete along with fly ash as fly ash can be used as a filler to provide enough bulk and surface area to our specimen to float. Secondly we will try to prove that by using glass beads as an alternative to the aggregate the property of concrete in flexure is enhancing as glass beads are less prone to fatigue. Thirdly we will try to show that use of glass beads as an makes it eco-friendly.